Implementing Comparative Method in Education With the case of Leaf Lettuce Irradiation Modes - Zheleznikova, Olga E. (2020)
The article presents the results of four series of experimental studies of irradiation efficiency of Moskovskii Parnikovyi leaf lettuce with general and special-purpose LED lamps (phyto-lamps) under various irradiation modes. The studies were conducted with an automated experimental irradiation device. The influence of the spectral compositions of LED radiation on the growth and development of Moskovskii Parnikovyi leaf lettuce is estimated. The studies have shown that LED phyto lamps are more effective in terms of productivity of Moskovskii Parnikovyi leaf lettuce compared to general-purpose LED lamps with equal electrical power consumption.